Rod-like core-shell structure nanoparticles, preparation method thereof and electrorheological elastomer

By using rod-shaped core-shell structure nanoparticles in the current variable elastomer and applying a magnetic field during the curing process, the problem of insufficient electric field strength is solved, and the energy storage modulus and relative current effect of the current variable elastomer are significantly improved, thus achieving Better mechanical properties.

CN119119582APending Publication Date: 2024-12-13HAI AN & TAIYUAN UNIV OF TECH ADVANCED MFG & INTELLIGENT EQUIP IND RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411233627.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing current variable elastomers are insufficient in the external electric field strength during the curing process, resulting in poor orientation and arrangement of dielectric particles, which limits the improvement of their mechanical properties, especially the energy storage modulus and relative current variation effect.

Method used

Using rod-shaped core-shell structure nanoparticles, including rod-shaped Fe3O4 nanoparticles and TiO2 coated on their surface, the energy storage modulus of the current-variable elastomer is enhanced and Relative current change effect.

Benefits of technology

The energy storage modulus of the current-variable elastomer reached 96.789kPa, and the relative current-variable effect reached 26.547%, which is better than the performance of nanoparticles filling in spherical core-shell structures, and significantly improves its mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119582A_ABST
    Figure CN119119582A_ABST
Patent Text Reader

Abstract

The invention provides a rod-like core-shell structure nanoparticle, a preparation method thereof and an electrorheological elastomer, and belongs to the technical field of electrorheological elastomers. The rodlike core-shell structure nano-particle provided by the invention comprises a rodlike ferroferric oxide nano-particle and titanium dioxide coated on the surface of the rodlike ferroferric oxide nano-particle. According to the invention, the rodlike ferroferric oxide nanoparticles are taken as the core, so that the rodlike core-shell structure nanoparticles form ordered arrangement under the action of a magnetic field in the elastomer curing process, the rodlike core-shell structure nanoparticles are easy to agglomerate through the coated titanium dioxide layer, and a thicker and denser particle chain structure is formed in the elastomer curing process; and the energy storage modulus and the relative electrorheological effect are improved. Compared with an elastomer filled with spherical core-shell structure nanoparticles, the electrorheological elastomer obtained by filling the elastomer matrix with the rod-like core-shell structure nanoparticles provided by the invention has better energy storage modulus and relative electrorheological effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrorheological elastomers, and in particular to a rod-shaped core-shell structure nanoparticle and a preparation method thereof, and an electrorheological elastomer. Background Art

[0002] Electrorheological elastomer is a kind of intelligent soft material that has emerged in recent years. It is composed of an elastic polymer matrix and polarizable micro or nanoparticles dispersed in the elastic polymer matrix. The mechanical properties of electrorheological elastomer can be continuously, rapidly and reversibly regulated by an external electric field. Macroscopically, under the same shear stress, the strain of the electrorheological elastomer will change with the change of the electric field strength. Electrorheological elastomer has overcome the shortcomings of electrorheological fluid, such as poor anti-sedimentation, easy leakage and poor structural adaptability, and has broad application prospects in the fields of artificial muscles, soft robots, control systems, etc.

[0003] Existing related research has proved that the electrorheological elastomer with oriented pre-structured particles has better field-induced mechanical effect. Therefore, in the preparation and molding process of electrorheological elastomer, it is necessary to solidify the elastomer matrix under the condition of an external electric field. At the same time, in order to ensure the effect of the particle orientation pre-structure, there are high requirements for the electric field intensity during the curing process of the elastomer.

[0004] However, due to the thickness of the elastomer sample itself and the insulation requirements of the mold, the distance between the two electrodes of the external electric field in the mold is usually large. In order to increase the strength of the external electric field, the applied voltage needs to be further increased. The increase in voltage can easily cause the air between the two electrodes to break down, causing the high voltage to be unable to continue to be applied, resulting in insufficient external electric field strength during the curing of the elastomer, and limited orientation of the dielectric particles. Although air breakdown is avoided after reducing the voltage, the electric field strength will be insufficient, making it difficult for the electric field strength of the electrorheological elastomer to meet the particle orientation requirements during the curing process. Limited by the orientation effect of the dielectric particles in the elastomer in the curing electric field, the comprehensive mechanical properties of the electrorheological elastomer, that is, the elastomer performance including the zero-field storage modulus and the relative electrorheological effect, need to be further improved.

[0005] Particles with electromagnetic dual-field response characteristics are used as dispersed phase particles. During the preparation and curing process of the elastomer, the magnetic response characteristics of the particles are used to form a better oriented arrangement pre-structure under an external magnetic field. During use, the electrical response characteristics of the particles are used. Using the elastomer as an electrorheological elastomer can give full play to its advantages. Summary of the invention

[0006] The object of the present invention is to provide a rod-shaped core-shell structure nanoparticle, a preparation method thereof and an electrorheological elastomer. The rod-shaped core-shell structure nanoparticle provided by the present invention has a rod-shaped core-shell structure, and the rod-shaped core-shell structure nanoparticle can be filled in an electrorheological elastomer to form an orderly filling in a matrix material through an external magnetic field, and the electrorheological elastomer has a good storage modulus and relative electrorheological effect.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a rod-shaped core-shell structure nanoparticle, comprising a rod-shaped Fe3O4 nanoparticle and a TiO2 coated on the surface of the rod-shaped Fe3O4 nanoparticle. 2。

[0009] Preferably, the length of the rod-shaped core-shell structured nanoparticles is 290 to 330 nm, and the diameter is 35 to 65 nm; the thickness of the TiO2 is 10 to 30 nm.

[0010] The present invention provides a method for preparing the rod-shaped core-shell structured nanoparticles described in the above technical solution, comprising the following steps:

[0011] (1) mixing rod-shaped Fe3O4 nanoparticles with an alcohol solvent and aqueous ammonia to obtain a dispersion;

[0012] (2) Adding the titanium compound solution to the dispersion obtained in step (1) to carry out a hydrolysis polymerization reaction to obtain rod-shaped core-shell structured nanoparticles.

[0013] Preferably, the mass concentration of ammonia water in step (1) is 6.5-8 kg / m 3 ; The ratio of the mass of rod-shaped Fe3O4 nanoparticles to the volume of ammonia water is (3~5)g:(7~10)mL.

[0014] Preferably, the speed of adding the titanium-containing compound solution in step (2) is 1.5 to 2 mL / min.

[0015] Preferably, the temperature of the hydrolysis polymerization reaction in step (2) is room temperature, and the time of the hydrolysis polymerization reaction is 22 to 26 hours.

[0016] The present invention provides an electrorheological elastomer, comprising an elastomer matrix and rod-shaped core-shell structured nanoparticles orderly filled in the elastomer matrix; the rod-shaped core-shell structured nanoparticles are the rod-shaped core-shell structured nanoparticles described in the above technical solution or the rod-shaped core-shell structured nanoparticles prepared by the preparation method described in the above technical solution.

[0017] Preferably, the volume fraction of the rod-shaped core-shell structure nanoparticles in the electrorheological elastomer is 10-35%.

[0018] The present invention provides a method for preparing the electrorheological elastomer described in the above technical solution, comprising: mixing an elastomer solution and rod-shaped core-shell structure nanoparticles, then adding a curing agent to perform curing under a magnetic field to obtain the electrorheological elastomer.

[0019] Preferably, the intensity of the magnetic field is 300-1000 mT.

[0020] The present invention provides a rod-shaped core-shell structure nanoparticle, comprising a rod-shaped Fe3O4 nanoparticle and TiO2 coated on the surface of the rod-shaped Fe3O4 nanoparticle. The present invention takes the rod-shaped Fe3O4 nanoparticle as the core, and the TiO2 layer coated on the surface makes the rod-shaped core-shell structure nanoparticle have the characteristic of polarization under an electric field. By applying a magnetic field during the curing process of the elastomer, the rod-shaped core-shell particles can form a more robust and dense particle chain structure than under the external electric field curing condition, and then show a stronger hindering effect on the movement of rubber molecular segments when the electrorheological elastomer is used, further improving the storage modulus and relative electrorheological effect. The results of the embodiment show that the storage modulus of the electrorheological elastomer obtained by filling the rod-shaped core-shell structure nanoparticles provided by the present invention in the elastomer matrix can reach 96.789kPa, and the relative electrorheological effect can reach 26.547%, which has better storage modulus and relative electrorheological effect than the elastomer filled with spherical core-shell structure nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 is a SEM image of the rod-shaped Fe3O4 nanoparticles in Example 1 of the present invention;

[0022] Figure 2 is a SEM image of the rod-shaped core-shell structure nanoparticles in Example 1 of the present invention;

[0023] Figure 3 This is a SEM image of the spherical Fe3O4 nanoparticles in Comparative Example 1 of the present invention;

[0024] Figure 4 This is a SEM image of the spherical core-shell structured nanoparticles in Comparative Example 1 of the present invention;

[0025] Figure 5 TEM image of the rod-shaped core-shell structure nanoparticles in Example 1 of the present invention;

[0026] Figure 6 The XRD diagram of the rod-shaped Fe3O4 nanoparticles and the rod-shaped core-shell structure nanoparticles in Example 1 of the present invention;

[0027] Figure 7 The XRD diagram of the spherical Fe3O4 nanoparticles and the spherical core-shell structure nanoparticles in Comparative Example 1 of the present invention;

[0028] Figure 8 The infrared spectra of the rod-shaped Fe3O4 nanoparticles and the rod-shaped core-shell structure nanoparticles in Example 1 of the present invention;

[0029] Fig. 9 The thermogravimetric analysis diagram of the rod-shaped Fe3O4 nanoparticles and the rod-shaped core-shell structure nanoparticles in Example 1 of the present invention; wherein a is the rod-shaped Fe3O4 nanoparticles, and b is the rod-shaped core-shell structure nanoparticles;

[0030] Fig.10 is a graph showing the relationship between the storage modulus of the electrorheological elastomers of application examples 1 to 3 of the present invention and the change of the electric field;

[0031] Fig.11 A graph showing the relationship between the relative electrorheological effect of the electrorheological elastomers of application examples 1 to 3 of the present invention and the change of the electric field;

[0032] Fig.12 It is a relationship diagram of the storage modulus of the electrorheological elastomers of application examples 3 to 5 of the present invention and comparative application examples 1 to 3 as a function of the electric field;

[0033] Fig.13 The figure is a relationship diagram of the relative electrorheological effect of the electrorheological elastomers of application examples 3 to 5 of the present invention and comparative application examples 1 to 3 as the electric field changes. DETAILED DESCRIPTION

[0034] The invention provides a rod-shaped core-shell structure nanoparticle, comprising a rod-shaped Fe3O4 nanoparticle and TiO2 coated on the surface of the rod-shaped Fe3O4 nanoparticle.

[0035] In the present invention, the length of the rod-shaped core-shell structure nanoparticles is preferably 290-330nm, more preferably 300-320nm; the diameter of the rod-shaped core-shell structure nanoparticles is preferably 35-65nm, more preferably 45-55nm; the thickness of the TiO2 is preferably 10-30nm, more preferably 15-25nm. The present invention limits the structure and size of the rod-shaped core-shell structure nanoparticles to the above range to ensure that the rod-shaped core-shell structure nanoparticles have good magnetic response while allowing the rod-shaped core-shell structure nanoparticles to agglomerate into a chain structure, thereby improving the storage modulus and relative electrorheological effect of the electrorheological elastomer.

[0036] The present invention uses rod-shaped Fe3O4 nanoparticles as the core, and the TiO2 layer coated on the surface makes the rod-shaped core-shell structure nanoparticles have polarizable characteristics under an electric field. By applying a magnetic field during the curing process of the elastomer, the rod-shaped core-shell particles can form a more robust and dense particle chain structure than under the external electric field curing conditions, thereby showing a stronger inhibitory effect on the movement of rubber molecular chain segments when the electrorheological elastomer is used, further improving the storage modulus and the relative electrorheological effect.

[0037] The present invention also provides a method for preparing the rod-shaped core-shell structured nanoparticles described in the above technical solution, comprising the following steps:

[0038] (1) mixing rod-shaped Fe3O4 nanoparticles with an alcohol solvent and aqueous ammonia to obtain a dispersion;

[0039] (2) Adding the titanium compound solution to the dispersion obtained in step (1) to carry out a hydrolysis polymerization reaction to obtain rod-shaped core-shell structured nanoparticles.

[0040] The invention mixes rod-shaped Fe3O4 nanoparticles with alcohol solvent and ammonia water to obtain a dispersion.

[0041] In the present invention, the method for preparing the rod-shaped Fe3O4 nanoparticles preferably comprises: mixing benzene, distilled water, ferrous salt, ferric salt and ethylenediamine and then performing a hydrothermal reaction to obtain rod-shaped Fe3O4 nanoparticles.

[0042] In the present invention, the volume ratio of benzene, distilled water and ethylenediamine is preferably (0.14-0.25):1:(0.11-0.20), more preferably (0.18-0.22):1:(0.12-0.15), and further preferably 0.2:1:0.125.

[0043] In the present invention, the ferrous salt preferably includes ferrous sulfate, ferrous chloride or ferrous carbonate; the ferric salt preferably includes ferric chloride, ferric sulfate or ferric nitrate.

[0044] In the present invention, the molar concentration of the ferrous salt in the mixed solution of benzene, distilled water, ferrous salt, ferric salt and ethylenediamine is preferably 0.017-0.021 mol / L, more preferably 0.019 mol / L.

[0045] In the present invention, the molar ratio of the ferrous salt to the ferric salt is preferably 1:(1.5-2.5), more preferably 1:2. The present invention limits the molar ratio of the ferrous salt to the ferric salt to the above range, which can help ensure that Fe 2+ and Fe 3+ Corresponding to the stoichiometric ratio of the two ions in the generated Fe3O4.

[0046] In the present invention, the addition amounts of benzene, distilled water, ferrous salt, ferric salt and ethylenediamine are limited to the above ranges to ensure uniform mixing of the raw materials, which is beneficial to the subsequent formation of rod-shaped Fe3O4 nanoparticles of uniform size.

[0047] In the present invention, the benzene, distilled water, ferrous salt, ferric salt and ethylenediamine are preferably mixed in the following manner: benzene and distilled water are first mixed, ferrous salt and ferric salt are added for second mixing, and ethylenediamine is added for third mixing.

[0048] The present invention has no particular limitation on the mixing method and mixing time of the first mixing, the second mixing and the third mixing, as long as the raw materials can be mixed uniformly.

[0049] In the present invention, the hydrothermal reaction is preferably carried out in a reactor. The present invention has no special limitation on the model of the reactor, and any reactor model commonly used by those skilled in the art can be used.

[0050] In the present invention, the temperature of the hydrothermal reaction is preferably 110-130°C, more preferably 120°C; the time of the hydrothermal reaction is preferably 18-22h, more preferably 20h. The present invention limits the temperature and time of the hydrothermal reaction to the above ranges to ensure that the reaction proceeds fully.

[0051] The present invention produces the following chemical reactions during the hydrothermal reaction:

[0052] Fe 2+ +2OH - →Fe(OH)2;Fe 3+ +3OH - →Fe(OH)3

[0053] 4Fe(OH)2+O2→4FeOOH+2H2O; Fe(OH)3→FeOOH+H2O

[0054] 2FeOOH+Fe 2+ →Fe3O4+2H +

[0055] In the present invention, after the hydrothermal reaction is completed, the product of the hydrothermal reaction is preferably cooled, centrifuged, washed, dried and ground in sequence to obtain rod-shaped Fe3O4 nanoparticles.

[0056] In the present invention, the cooling is preferably natural cooling.

[0057] The present invention has no special limitation on the centrifugal operation, as long as the solid-liquid separation of the hydrothermal reaction product can be achieved.

[0058] In the present invention, the solvent used for the washing is preferably anhydrous ethanol; the number of washing is preferably 2 to 3 times. The present invention has no special limitation on the specific operation of the washing, and the washing operation well known to those skilled in the art can be used to wash the surface cleanly.

[0059] In the present invention, the drying is preferably carried out under vacuum conditions; the present invention has no special limitation on the vacuum conditions, as long as the washed product is not oxidized.

[0060] In the present invention, the drying temperature is preferably 55-65°C, more preferably 60°C; the drying time is preferably 3-5h, more preferably 4h. The present invention limits the drying temperature and time to the above ranges to ensure that dry rod-shaped Fe3O4 nanoparticles are obtained.

[0061] The present invention has no special limitation on the grinding, as long as the agglomerated particles can be dispersed.

[0062] The present invention adopts the above-mentioned preparation method to obtain rod-shaped Fe3O4 nanoparticles with a length of 270-310nm and a diameter of 25-45nm, which is beneficial to the subsequent magnetic / electric response of the rod-shaped core-shell structure nanoparticles in the elastomer.

[0063] In the present invention, the mass concentration of the ammonia water is preferably 6.5 to 8 kg / m 3 , more preferably 7.2 kg / m 3 In the present invention, the ratio of the mass of the rod-shaped Fe3O4 nanoparticles to the volume of ammonia water is preferably (3-5) g: (7-10) mL, more preferably (4-5) g: (8-10) mL, and even more preferably 5 g: 10 mL. The present invention limits the concentration of ammonia water, the mass of the rod-shaped Fe3O4 nanoparticles and the volume of ammonia water to the above range to ensure that the rod-shaped Fe3O4 nanoparticles are modified with NH 4+ ions, which is beneficial for the subsequent coating of TiO2 on the surface of rod-shaped Fe3O4 nanoparticles, making ≡TiO- easier to adsorb on the particle surface.

[0064] In the present invention, the alcohol solvent preferably includes anhydrous ethanol, propanol or n-butanol, and more preferably anhydrous ethanol. The present invention has no particular limitation on the amount of the alcohol solvent added to the dispersion, as long as the amount can disperse the rod-shaped Fe3O4 nanoparticles. In a specific embodiment of the present invention, the ratio of the mass of the rod-shaped Fe3O4 nanoparticles to the volume of the alcohol solvent is 5g:lL.

[0065] In the present invention, the mixing of the rod-shaped Fe3O4 nanoparticles, the alcohol solvent and the ammonia water is preferably performed by ultrasound; the ultrasound time is preferably 8 to 12 minutes, more preferably 10 minutes. The present invention has no particular limitation on the frequency of the ultrasound, and the rod-shaped Fe3O4 nanoparticles, the alcohol solvent and the ammonia water can be uniformly mixed using the ultrasound power commonly used by those skilled in the art.

[0066] In the present invention, after obtaining the dispersion, the dispersion is preferably placed in a 40° C. water bath for mechanical stirring to ensure uniform dispersion, and then taken out of the water bath for subsequent addition of the titanium compound solution to carry out hydrolysis polymerization at room temperature.

[0067] After obtaining the dispersion, the present invention adds the titanium compound solution into the dispersion to carry out hydrolysis polymerization reaction to obtain rod-shaped core-shell structure nanoparticles.

[0068] In the present invention, the titanium-containing compound in the titanium-containing compound solution preferably includes tetrabutyl titanate, titanium tetrachloride, tetraethyl titanate or tetraisopropyl titanate; the solvent in the titanium-containing compound solution is preferably anhydrous ethanol. In the present invention, the volume ratio of the titanium-containing compound to the solvent in the titanium-containing compound solution is preferably 1: (8-12), more preferably 1: 10. The present invention limits the type of titanium-containing compound and the volume ratio of the titanium-containing compound to the solvent to the above range so that TiO2 can be well coated on the rod-shaped Fe3O4 nanoparticles.

[0069] In the present invention, the speed of adding the titanium-containing compound solution is preferably 1.5-2 mL / min, more preferably 1.7-1.9 mL / min, and further preferably 1.8 mL / min. The addition speed of the titanium-containing compound solution to the dispersion is limited to the above range so that the titanium-containing compound can be slowly and evenly hydrolyzed, so that the hydrolyzate of the titanium-containing compound can be evenly attached and polymerized on the surface of the rod-shaped Fe3O4 nanoparticles.

[0070] In the present invention, the volume ratio of the titanium-containing compound solution to the dispersion is preferably (1-2):5, more preferably (1.2-1.8):5, and further preferably 1.5:5. The present invention limits the volume ratio of the titanium-containing compound solution to the dispersion to the above range so that the hydrolyzate of the titanium-containing compound can be fully attached and polymerized on the surface of the rod-shaped Fe3O4 nanoparticles, thereby improving the storage modulus and relative electrorheological effect of the electrorheological elastomer.

[0071] In the present invention, the temperature of the hydrolysis polymerization reaction is preferably room temperature; the time of the hydrolysis polymerization reaction is preferably 22 to 26 hours, more preferably 24 hours. The present invention limits the temperature and time of the hydrolysis polymerization reaction to the above ranges to ensure that the reaction proceeds fully.

[0072] In the hydrolysis polymerization process of the present invention, taking butyl titanate as an example of the titanium-containing compound, the following chemical reaction occurs:

[0073] ≡TiOC4H9+H2O→≡Ti-OH+C4H9OH

[0074] ≡Ti-OH+HO-Ti≡→≡Ti-O-Ti≡+H2O

[0075] In the present invention, after the hydrolysis polymerization reaction is completed, the product of the hydrolysis polymerization reaction is preferably separated, washed and dried in sequence to obtain rod-shaped core-shell structured nanoparticles.

[0076] In the present invention, the separation is preferably carried out by using a magnet to separate the product of the hydrolysis polymerization reaction to obtain a precipitate. In the present invention, the specific operation of the separation is to place a magnet outside the container used for the hydrolysis polymerization reaction to adsorb the precipitate.

[0077] In the present invention, the solvent used for the washing is preferably anhydrous ethanol. The present invention has no particular limitation on the number of washings, as long as the precipitate can be washed cleanly.

[0078] In the present invention, the drying temperature is preferably 35-45°C, more preferably 40°C; the drying time is preferably 22-26h, more preferably 24h. The present invention limits the drying temperature and time to the above ranges to ensure that dry rod-shaped core-shell structured nanoparticles are obtained.

[0079] The present invention also provides an electrorheological elastomer, comprising an elastomer matrix and rod-shaped core-shell structure nanoparticles orderly filled in the elastomer matrix.

[0080] In the present invention, the rod-shaped core-shell structured nanoparticles are the rod-shaped core-shell structured nanoparticles described in the above technical solution or the rod-shaped core-shell structured nanoparticles prepared by the preparation method described in the above technical solution.

[0081] In the present invention, the volume fraction of the rod-shaped core-shell structure nanoparticles in the electrorheological elastomer is preferably 10 to 35%, more preferably 15 to 30%, and further preferably 20 to 30%. The present invention limits the volume fraction of the rod-shaped core-shell structure nanoparticles in the electrorheological elastomer to the above range so that the electrorheological elastomer can have a good storage modulus and relative electrorheological effect.

[0082] The present invention also provides a method for preparing the electrorheological elastomer described in the above technical solution, comprising: mixing an elastomer solution and rod-shaped core-shell structure nanoparticles, then adding a curing agent and curing under a magnetic field to obtain the electrorheological elastomer.

[0083] In the present invention, the elastomer solution is preferably a mixed solution of vulcanized silicone rubber and silicone oil; the vulcanized silicone rubber is preferably room temperature vulcanized rubber; the silicone oil is preferably dimethyl silicone oil; the viscosity of the dimethyl silicone oil is preferably 10 to 200 mPa·s. The present invention limits the type of vulcanized silicone rubber, the type of silicone oil and the viscosity to the above range to ensure that the silicone oil and the vulcanized silicone rubber have good miscibility and dispersibility, and at the same time ensure that the silicone oil has a strong solubilizing effect on the silicone rubber, and can play a good softening effect on the silicone rubber matrix.

[0084] In the present invention, the mass ratio of the vulcanized silicone rubber to the silicone oil is preferably 1: (0.8-1.2), more preferably 1: 1. In the present invention, too little silicone oil will affect the amount of rod-shaped core-shell particles added later, and too much silicone oil will affect the curing properties of the silicone rubber itself. The present invention limits the mass ratio of the vulcanized silicone rubber to the silicone oil to the above range so that the two can have better overall fluidity and particle filling after being mixed.

[0085] In the present invention, the amount of the rod-shaped core-shell structured nanoparticles added is preferably 10-35% of the total volume of the elastomer solution and the rod-shaped core-shell structured nanoparticles, more preferably 15-30%, and further preferably 20-30%. The present invention limits the amount of the rod-shaped core-shell structured nanoparticles added to the above range so that the electrorheological elastomer can have a good storage modulus and relative electrorheological effect.

[0086] In the present invention, the mass ratio of the elastomer solution to the curing agent is preferably 200:(6-10), more preferably 200:(7-9). The present invention limits the mass ratio of the elastomer solution to the curing agent to the above range to ensure the curing of the elastomer.

[0087] In a specific embodiment of the present invention, the curing agent is a mixed solution of tetraethyl orthosilicate and dibutyltin dilaurate; the mass ratio of tetraethyl orthosilicate to dibutyltin dilaurate is 3:1.

[0088] In the present invention, the intensity of the magnetic field is preferably 300-1000 mT, more preferably 600-1000 mT, and further preferably 800-1000 mT. The present invention limits the intensity of the magnetic field to the above range to further improve the storage modulus and relative electrorheological effect of the electrorheological elastomer.

[0089] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0090] Example 1

[0091] A rod-shaped core-shell structure nanoparticle, comprising a rod-shaped Fe3O4 nanoparticle and TiO2 coated on the surface of the rod-shaped Fe3O4 nanoparticle; the rod-shaped core-shell structure nanoparticle has a length of 290 to 330 nm and a diameter of 35 to 65 nm; the thickness of the TiO2 is 10 to 30 nm;

[0092] The method for preparing the rod-shaped core-shell structure nanoparticles comprises the following steps:

[0093] (1) The rod-shaped Fe3O4 nanoparticles were ultrasonically mixed with anhydrous ethanol and ammonia water for 20 minutes to obtain a dispersion, and then the dispersion was placed in a 40°C water bath for mechanical stirring for standby use; the mass concentration of the ammonia water was 7.2 kg / m 3 ; The ratio of the mass of the rod-shaped Fe3O4 nanoparticles, the volume of anhydrous ethanol and the volume of ammonia water is 5g:lL:10mL;

[0094] (2) adding a titanium-containing compound solution to the dispersion obtained in step (1) at a rate of 1.8 mL / min to carry out a hydrolysis polymerization reaction at room temperature for 24 hours, separating the precipitate with a magnet, washing it with anhydrous ethanol, and drying it at 40° C. for 24 hours to obtain rod-shaped core-shell structured nanoparticles; the titanium-containing compound in the titanium-containing compound solution is tetrabutyl titanate, and the solvent is anhydrous ethanol; the volume ratio of tetrabutyl titanate to anhydrous ethanol is 1:10; the volume ratio of the titanium-containing compound solution to the dispersion is 2:5;

[0095] The preparation method of the rod-shaped Fe3O4 nanoparticles is as follows: after benzene and distilled water are mixed for the first time, ferrous sulfate heptahydrate and ferric chloride hexahydrate are added for the second mixing (stirring for 5 minutes), and finally ethylenediamine is added for the third mixing (stirring for 5 minutes), and then a hydrothermal reaction is carried out at 120°C for 20 hours. After naturally cooling to room temperature, the hydrothermal reaction product is centrifuged, washed twice with anhydrous ethanol, and then vacuum dried at 60°C for 4 hours and ground to obtain rod-shaped Fe3O4 nanoparticles; the volume ratio of the benzene, distilled water and ethylenediamine is 0.2:1:0.125; the molar concentration of the ferrous sulfate heptahydrate in the mixed solution of benzene, distilled water, ferrous salt, ferric chloride hexahydrate and ethylenediamine is 0.019 mol / L; the molar ratio of the ferrous sulfate heptahydrate and ferric chloride hexahydrate is 1:2.

[0096] Comparative Example 1

[0097] A method for preparing spherical core-shell structured nanoparticles comprises the following steps:

[0098] (a) 1.35 g of FeCl3 was dissolved in 70 mL of ethylene glycol, and 3.85 g of ammonium acetate was added and stirred for 30 minutes to obtain a mixed solution A;

[0099] (b) subjecting the mixed solution A obtained in step (a) to a hydrothermal reaction at 200° C. for 12 h, cooling naturally to room temperature, centrifuging the hydrothermal reaction product, washing twice with anhydrous ethanol, and then vacuum drying at 60° C. for 4 h and grinding to obtain spherical Fe3O4 nanoparticles;

[0100] (c) dispersing 200 mg of the spherical Fe3O4 nanoparticles obtained in step (b) in 50 mL of anhydrous ethanol, adding 0.4 mL of aqueous ammonia, and ultrasonically dispersing for 40 minutes to obtain a mixed solution B;

[0101] (d) 1 mL of tetrabutyl titanate and 20 mL of anhydrous ethanol were mixed and magnetically stirred for 30 minutes to obtain a mixed solution C;

[0102] (e) adding the mixed solution C obtained in step (d) to the mixed solution B obtained in step (c) at a rate of 1.8 mL / min to carry out a hydrolysis polymerization reaction at room temperature for 24 hours, separating the precipitate with a magnet, washing it with anhydrous ethanol, and drying it at 40° C. for 24 hours to obtain spherical core-shell structured nanoparticles.

[0103] Application Example 1

[0104] An electrorheological elastomer, comprising an elastomer matrix and rod-shaped core-shell structured nanoparticles orderly filled in the elastomer matrix; the rod-shaped core-shell structured nanoparticles are the rod-shaped core-shell structured nanoparticles prepared in Example 1; the volume fraction of the rod-shaped core-shell structured nanoparticles in the electrorheological elastomer is 10%;

[0105] The preparation method of the electrorheological elastomer is as follows: an elastomer solution and rod-shaped core-shell structure nanoparticles are mixed, and then a curing agent (a mixed solution of ethyl orthosilicate and dibutyltin dilaurate in a mass ratio of 3:1) is added to cure under a 300mT magnetic field to obtain an electrorheological elastomer; the elastomer solution is a mixed solution of room temperature vulcanized silicone rubber and dimethyl silicone oil with a viscosity of 100mPa·s; the mass ratio of the room temperature vulcanized silicone rubber to the dimethyl silicone oil is 1:1; the amount of the rod-shaped core-shell structure nanoparticles added is 10% of the total volume of the elastomer solution and the rod-shaped core-shell structure nanoparticles; the mass ratio of the elastomer solution to the curing agent is 200:8;

[0106] Application Example 2

[0107] The difference between Application Example 2 and Application Example 1 is that the magnetic field strength is 600 mT, and the rest is the same as Application Example 1.

[0108] Application Example 3

[0109] The difference between Application Example 3 and Application Example 1 is that the magnetic field strength is 1000 mT, and the rest is the same as Application Example 1.

[0110] Application Example 4

[0111] The difference between Application Example 4 and Application Example 3 is that the volume fraction of the rod-shaped core-shell structure nanoparticles in the electrorheological elastomer is 15%, and the rest is the same as Application Example 3.

[0112] Application Example 5

[0113] The difference between Application Example 5 and Application Example 3 is that the volume fraction of the rod-shaped core-shell structure nanoparticles in the electrorheological elastomer is 20%, and the rest is the same as Application Example 3.

[0114] Comparative application example 1

[0115] An electrorheological elastomer, comprising an elastomer matrix and spherical core-shell structured nanoparticles orderly filled in the elastomer matrix; the spherical core-shell structured nanoparticles are the spherical core-shell structured nanoparticles prepared in Comparative Example 1; the volume fraction of the spherical core-shell structured nanoparticles in the electrorheological elastomer is 10%;

[0116] The preparation method of the electrorheological elastomer is different from that of Application Example 3 only in that the rod-shaped core-shell structure nanoparticles are replaced with spherical core-shell structure nanoparticles, and the other preparation steps are the same as those of Application Example 3;

[0117] Comparative Application Example 2

[0118] The only difference between Comparative Application Example 2 and Comparative Application Example 1 is that the volume fraction of the spherical core-shell structure nanoparticles in the electrorheological elastomer is 15%, and the rest is the same as Comparative Application Example 1.

[0119] Comparative Application Example 3

[0120] The only difference between Comparative Application Example 3 and Comparative Application Example 1 is that the volume fraction of the spherical core-shell structure nanoparticles in the electrorheological elastomer is 20%, and the rest is the same as Comparative Application Example 1.

[0121] The rod-shaped Fe3O4 nanoparticles and the rod-shaped core-shell structure nanoparticles in Example 1 and the spherical Fe3O4 nanoparticles and the spherical core-shell structure nanoparticles in Comparative Example 1 were observed using a scanning electron microscope;

[0122] The rod-shaped core-shell structure nanoparticles in Example 1 were observed using a transmission electron microscope;

[0123] The rod-shaped Fe3O4 nanoparticles and rod-shaped core-shell structure nanoparticles in Example 1 and the spherical Fe3O4 nanoparticles and spherical core-shell structure nanoparticles in Comparative Example 1 were analyzed by X-ray diffractometer;

[0124] The rod-shaped Fe3O4 nanoparticles and the rod-shaped core-shell structure nanoparticles in Example 1 were analyzed by infrared spectrometer;

[0125] The rod-shaped Fe3O4 nanoparticles and rod-shaped core-shell structure nanoparticles in Example 1 and the spherical Fe3O4 nanoparticles and spherical core-shell structure nanoparticles in Comparative Example 1 were analyzed using a thermogravimetric analyzer;

[0126] The storage modulus of the electrorheological elastomer in the corresponding application example and the comparative application example is tested under different electric fields using a rotational rheometer;

[0127] The relative electrorheological effect of the electrorheological elastomers in the corresponding examples and comparative application examples was tested under different electric fields using a rotational rheometer.

[0128] The SEM image of the rod-shaped Fe3O4 nanoparticles in Example 1 is as follows Figure 1 As shown, from Figure 1 It can be seen that the length of the rod-like Fe3O4 nanoparticles is 290±20nm and the diameter is 35±10nm.

[0129] The SEM image of the rod-shaped core-shell structure nanoparticles in Example 1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that the length of the core-shell structured nanoparticles is 310±20nm and the diameter is 50±15nm.

[0130] The SEM image of the spherical Fe3O4 nanoparticles in Comparative Example 1 is as follows: Figure 3 As shown, from Figure 3 It can be seen that the diameter of the spherical Fe3O4 particles is 240±30nm.

[0131] The SEM image of the spherical core-shell structure nanoparticles in Comparative Example 1 is as follows: Figure 4 As shown, from Figure 4 It can be seen that the diameter of the spherical core-shell structured nanoparticles is 300±10nm.

[0132] The TEM image of the rod-shaped core-shell structure nanoparticles in Example 1 is as follows: Figure 5 As shown, from Figure 5 It can be seen that the core-shell structured nanoparticles are rod-shaped core-shell structures, and the thickness of the TiO2 as the coating layer is 10 to 30 nm.

[0133] The XRD patterns of the rod-shaped Fe3O4 nanoparticles and rod-shaped core-shell structure nanoparticles in Example 1 are as follows: Figure 6 As shown, from Figure 6 It can be seen that the product composition is Fe3O4. After coating with TiO2, the diffraction peak intensity is significantly reduced. This is due to the influence of the TiO2 coating on the surface of Fe3O4 particles, which indirectly indicates that TiO2 has been successfully coated on the surface of Fe3O4.

[0134] The XRD patterns of the spherical Fe3O4 nanoparticles and spherical core-shell nanoparticles in Comparative Example 1 are as follows: Figure 7 As shown, from Figure 7 It can be seen that the product phase is Fe3O4, and the diffraction peak intensity is significantly reduced after coating with TiO2.

[0135] The infrared spectra of the rod-shaped Fe3O4 nanoparticles and rod-shaped core-shell structure nanoparticles in Example 1 are as follows: Figure 8 As shown, from Figure 8 It can be seen that in the rod-shaped Fe3O4 spectrum, 580cm -1 The characteristic peak of Fe-O stretching vibration appeared at 3000 cm -1 Up to 3500cm -1 Range and 1640cm -1 The characteristic peaks at 800cm-1 are caused by OH stretching vibration and bending vibration, which indicates that there are abundant -OH on the surface of the particles. -1 Up to 900cm -1 The absorption peak in the range corresponds to the bending vibration of a single methyl group on the benzene ring; 627cm -1 The characteristic peak at comes from the stretching vibration of Ti-O-Ti; the appearance of new characteristic peaks in the rod-like core-shell structured nanoparticles proves that TiO2 has covered the Fe3O4 surface.

[0136] The thermogravimetric analysis of the rod-shaped Fe3O4 nanoparticles and rod-shaped core-shell structure nanoparticles in Example 1 is shown in FIG. Fig. 9 As shown, a is a rod-shaped Fe3O4 nanoparticle, b is a rod-shaped core-shell structure nanoparticle, Fig. 9It can be seen that the first mass loss occurred from room temperature to 100℃, which was caused by the evaporation of water adsorbed on the surface of the particles; then between 200℃ and 300℃, the mass loss of this process was related to the thermal decomposition of organic groups on the surface of the particles; finally, as the temperature continued to rise to 900℃, a small amount of unreacted precursors remaining on the surface of the two particles and TiO2 on the surface of the rod-shaped core-shell structured nanoparticles were thermally decomposed. In the end, the residual amount of Fe3O4 particles was 90.9% and the residual amount of Fe3O4 particles was 80.8%. Among them, the residual amount of the rod-shaped core-shell structured nanoparticles at the beginning of the third stage was 87.3%, so the loss amount in the third stage was 6.5%. This result further confirmed that TiO2 was successfully coated on the surface of the rod-shaped Fe3O4 particles.

[0137] The relationship between the storage modulus of the electrorheological elastomer of application examples 1 to 3 and the change of the electric field is shown in the figure Fig.10 As shown in Table 1, the storage modulus data are shown in Table 1 and Fig.10 It can be seen that as the magnetic field intensity increases, the storage modulus of the electrorheological elastomer increases with the increase of the test electric field intensity. This is because the magnetic response characteristics of the particles are used to form a better oriented arrangement prestructure under the external field strength during the preparation and curing process. The greater the magnetic field intensity, the better the oriented arrangement prestructure of the matrix.

[0138] Table 1 Data on the change of storage modulus of electrorheological elastomers in application examples 1 to 3 with electric field

[0139]

[0140]

[0141] The relationship between the relative electrorheological effect of the electrorheological elastomers of application examples 1 to 3 and the change of the electric field is shown in the figure below: Fig.11 The relative electrorheological effect data are shown in Table 2. From Table 2 and Fig.11 It can be seen that the relative electrorheological effect of each elastomer increases with the increase of electric field strength and magnetic field strength.

[0142] Table 2 Data on the relative electrorheological effect of the electrorheological elastomers of application examples 1 to 3 as a function of the electric field

[0143]

[0144] The relationship between the storage modulus of the electrorheological elastomers of application examples 3 to 5 and comparative application examples 1 to 3 and the change of the electric field is shown in the figure Fig.12 As shown in Table 3, the storage modulus data are shown in Table 3 and Fig.12 It can be seen that when the volume fraction of the filling particles is the same, the storage modulus of the elastomer filled with rod-shaped core-shell nanoparticles is always higher than that of the elastomer filled with spherical particles.

[0145] Table 3 Data on the change of storage modulus of electrorheological elastomers in application examples 3 to 5 and comparative application examples 1 to 3 with electric field

[0146]

[0147] The relationship between the relative electrorheological effect of the electrorheological elastomers of application examples 3 to 5 and comparative application examples 1 to 3 and the change of electric field is shown in the figure Fig.13 The relative electrorheological effect data are shown in Table 4. Fig.13 It can be seen that, except for the particle volume fraction of 10%, the elastomer filled with rod-shaped particles has a higher relative electrorheological effect than the elastomer filled with spherical particles under other conditions.

[0148] Table 4 Data on the relative electrorheological effect of the electrorheological elastomers of application examples 3 to 5 and comparative application examples 1 to 3 as a function of the electric field

[0149]

[0150] The rod-shaped core-shell structured nanoparticles provided by the present invention have a length of 260 to 310 nm and a diameter of 25 to 45 nm. The thickness of TiO2 coated on the surface of the rod-shaped Fe3O4 nanoparticles is 10 to 30 nm. The storage modulus of the electrorheological elastomer obtained by filling the rod-shaped core-shell structured nanoparticles in an elastomer matrix can reach 96.789 kPa, and the relative electrorheological effect can reach 26.547%. Compared with the elastomer filled with spherical core-shell structured nanoparticles, the electrorheological elastomer has better storage modulus and relative electrorheological effect.

[0151] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A rod-shaped core-shell structure nanoparticle, comprising a rod-shaped Fe3O4 nanoparticle and a TiO2 coated on the surface of the rod-shaped Fe3O4 nanoparticle. 2。 2. The rod-shaped core-shell structure nanoparticle according to claim 1, characterized in that: The length of the rod-shaped core-shell structure nanoparticles is 290-330 nm, and the diameter is 35-65 nm; the thickness of the TiO2 is 10-30 nm.

3. The method for preparing the rod-shaped core-shell structure nanoparticles according to claim 1 or 2, comprising the following steps: (1) mixing rod-shaped Fe3O4 nanoparticles with an alcohol solvent and aqueous ammonia to obtain a dispersion; (2) Adding the titanium compound solution to the dispersion obtained in step (1) to carry out a hydrolysis polymerization reaction to obtain rod-shaped core-shell structured nanoparticles.

4. The preparation method according to claim 3, characterized in that: The mass concentration of ammonia water in step (1) is 6.5-8 kg / m 3 ; The ratio of the mass of rod-shaped Fe3O4 nanoparticles to the volume of ammonia water is (3~5)g:(7~10)mL.

5. The preparation method according to claim 3, characterized in that: The speed of adding the titanium compound solution in step (2) is 1.5-2 mL / min.

6. The preparation method according to claim 3, characterized in that: The temperature of the hydrolysis polymerization reaction in the step (2) is room temperature, and the time of the hydrolysis polymerization reaction is 22 to 26 hours.

7. An electrorheological elastomer, comprising an elastomer matrix and rod-shaped core-shell structured nanoparticles orderly filled in the elastomer matrix; the rod-shaped core-shell structured nanoparticles are the rod-shaped core-shell structured nanoparticles according to claim 1 or 2 or the rod-shaped core-shell structured nanoparticles prepared by the preparation method according to any one of claims 3 to 6.

8. The electrorheological elastomer according to claim 7, characterized in that: The volume fraction of the rod-shaped core-shell structure nanoparticles in the electrorheological elastomer is 10-35%.

9. The method for preparing the electrorheological elastomer according to claim 7 or 8, comprising: The elastomer solution and rod-shaped core-shell structured nanoparticles are mixed, and then a curing agent is added to perform curing under a magnetic field to obtain an electrorheological elastomer.

10. The preparation method according to claim 9, characterized in that: The intensity of the magnetic field is 300-1000 mT.